EVIDENCE FOR A ROLE OF CYCLIC AMP IN NEUROMUSCULAR TRANSMISSION - Goldberg, Alfred L. (1969)
Experiments were undertaken to determine if the effects of epinephrine in promoting neuromuscular transmission were mediated by adenosine 3′:5′-cyclic phosphate (cyclic AMP). Dibutyryl cyclic AMP and the methyl xanthines, theophylline and caffeine (which inhibit cyclic AMP hydrolysis), were found to increase the amplitude of the end plate potential in the isolated rat diaphragm. Like epinephrine (which is known to promote cyclic AMP synthesis), these agents appear to facilitate the release of acetylcholine from the motor neuron. This interpretation is supported by the observation that theophylline and dibutyryl cyclic AMP markedly increased the frequency but not the amplitude of the spontaneous miniature end plate potentials. In addition, these drugs increased the number of transmitter packets released in response to nerve stimulation. These results are consistent with the view that cyclic AMP plays a role in the release of acetylcholine and in the “defatiguing effect” of epinephrine.